Educational activities with the elderly in vulnerable situations - Deyla Moura Ramos Isoldi; Ana Michele de Farias Cabral; Clélia Albino Simpson (Universidade Federal do Ceará, 2015)
This study aimed at analyzing the knowledge of the elderly on the prevention of AIDS before and after the practice of education in health. This is a quasi-experimental study with a quantitative approach, performed in the Social Assistance Reference Centers, with 60 seniors. It was developed in Parnamirim, RN, Brazil, from February to June 2014. Data were collected through a questionnaire with closed questions about AIDS. In principle, most patients (61.6%) said they did not know what AIDS was, but this soon became reality after conducting a dialog lecture as a health education tool. There was a statistically significant difference. We conclude that education about AIDS is important to adopt a collective vision on the various socio-cultural contexts in which the elderly are inserted.